Numerical Study of the Effect of Notches on Main Cooling Water Pump Shaft Failure - Muhammad Firda Fattahuddian; Achmad Syaifudin (Eduvest - Journal of Universal Studies, 2026)
The Main Cooling Water Pump (MCWP) is critical in geothermal plants, since failure reduces capacity and increases downtime. This study investigates the fatigue failure of an ASTM A276 Type 316 stainless-steel MCWP shaft at an Indonesian geothermal plant, fractured by a grinding notch from overhaul. The unresolved problem is that the notch was identified only visually, without quantitative stress-concentration, fatigue-life, or numerical validation for repair-radius decisions. A Palmgren–Miner cumulative-damage analysis across startup, steady-state, and shutdown phases shows the baseline notch (r = 0.735 mm; Kts = 3.98) yields Dtotal = 0.6338 at 720 days, while D = 1 requires r ≈ 0.634–0.655 mm, only 14% sharper than baseline. ANSYS Mechanical 2025 R2 simulations across five repair radii (r = 4, 6, 8, 10, 11 mm) revealed a U-shaped Peterson-chart-versus-FEA deviation from a partial-arc effect: since repair depth is limited to 3 mm, the transition-arc fraction drops from 100% at baseline to 48.1% at the largest radius. The novelty of this study is characterizing this partial-arc mechanism quantitatively, distinct from the r/d-based chart deviations reported in prior work. For maintenance and asset management, stress reduction increases with radius up to r = 11 mm, while r = 6 mm marks the smallest chart-to-FEA deviation, which grows again at larger radii; a 0.1 mm radius change shifts damage from 63% to 100% of life, precise enough to guide repair-radius and inspection intervals. By quantifying this partial-arc limit on chart reliability, the study gives maintenance engineers a defensible, data-driven basis for repair-radius selection.